Penafsiran Ayat–Ayat Amar Ma’ruf Nahi Munkar menurut Muhammad Fethullah Gülen - Muslim Djuned; Pinar Ozdemir (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2019)
Amar ma'rūf nahi munkar is the command of Allah swt. to invite to the good things and prevent the bad for society. Many interpreters have explained the meaning of the verses amar ma'rūf nahi munkar. Fethullah Gülen is a character who tries to give an interpretation of the verse by relating it to the reality of people's lives. This paper discusses the verses of amar ma'ruf nahi munkar interpreted by Muhammad Fethullah Gülen and issues surrounding the position of enforcing amar ma'rūf nahi munkar. This research is a descriptive literature study, wanting to describe the figure of Gulen who wants to be researched based on facts from existing news, books, and magazines. The results showed that Gülen classified the interpretation of the verses of amar ma'ruf nahi munkar in 3 parts. First, amar ma'rūf nahi munkar as the goal of life. Second, amar ma'ruf nahi munkar as a sign of a believer. Third, enforce the commandments of ma'rf nahi munkar in accordance with nature. According to Gülen, people who carry out this sacred task well, then they will be protected by Allah from all disasters that come from heaven or earth, even though the number of people who carry out this task is not much. Meanwhile, those who forget this task are feared to die in a state of hypocrisy, for neglecting the task that Allah has assigned to every Muslim. Amar ma’rūf nahi munkar merupakan perintah Allah swt. untuk mengajak kepada hal-hal yang baik dan mencegah yang buruk bagi masyarakat. Banyak penafsir yang telah menjelaskan makna ayat-ayat amar ma’rūf nahi munkar. Fethullah Gülen merupakan seorang tokoh yang mencoba memberi penafsiran ayat tersebut dengan mengaitkannya pada realitas kehidupan masyarakat. Tulisan ini membahas ayat-ayat amar ma’ruf nahi munkar yang ditafsirkan oleh Muhammad Fethullah Gülen dan persoalan seputar kedudukan menegakkan amar ma’rūf nahi munkar. Penelitian ini bersifat kajian kepustakaan yang bersifat deskriptif, ingin menggambarkan sosok Gulen yang ingin diteliti berdasarkan fakta dari berita, buku, dan majalah yang ada. Hasil penelitian menunjukkan bahwa Gülen mengklasifikasikan penafsiran ayat-ayat amar ma’ruf nahi munkar dalam 3 bagian. Pertama, amar ma’rūf nahi munkar sebagai tujuan hidup. Kedua, amar ma’ruf nahi munkar sebagai tanda orang mukmin. Ketiga, menegakkan amar ma’rūf nahi munkar sesuai dengan fitrah. Menurut Gülen, masyarakat yang melakukan tugas suci ini dengan baik, maka mereka itu akan dilindungi Allah dari segala bencana yang datangnya dari langit atau bumi, meskipun jumlah orang yang menjalankan tugas ini tidak banyak. Sedangkan yang melupakan tugas ini, dikhawatirkan akan meninggal dalam keadaan munafik, karena melalaikan tugas yang dibebankan Allah kepada setiap orang Muslim.